Combined endobronchial and esophageal endosonography for the diagnosis and staging of lung cancer: European Society of Gastrointestinal Endoscopy (ESGE) Guideline, in cooperation with the European Respiratory Society (ERS) and the European Society of Thoracic Surgeons (ESTS) - Vilmann, Peter; Herth, Felix (Endoscopy, 2015)
This is an official guideline of the European Society of Gastrointestinal Endoscopy (ESGE), produced in cooperation with the European Respiratory Society (ERS) and the European Society of Thoracic Surgeons (ESTS). It addresses the benefit and burden associated with combined endobronchial and esophageal mediastinal nodal staging of lung cancer. The Scottish Intercollegiate Guidelines Network (SIGN) approach was adopted to define the strength of recommendations and the quality of evidence.The article has been co-published with permission in the European Journal of Cardio-Thoracic Surgery and the European Respiratory Journal. Recommendations 1 For mediastinal nodal staging in patients with suspected or proven non-small-cell lung cancer (NSCLC) with abnormal mediastinal and/or hilar nodes at computed tomography (CT) and/or positron emission tomography (PET), endosonography is recommended over surgical staging as the initial procedure (Recommendation grade A). The combination of endobronchial ultrasound with real-time guided transbronchial needle aspiration (EBUS-TBNA) and endoscopic (esophageal) ultrasound with fine needle aspiration, with use of a gastrointestinal (EUS-FNA) or EBUS (EUS-B-FNA) scope, is preferred over either test alone (Recommendation grade C). If the combination of EBUS and EUS-(B) is not available, we suggest that EBUS alone is acceptable (Recommendation grade C). Subsequent surgical staging is recommended, when endosonography does not show malignant nodal involvement (Recommendation grade B). 2 For mediastinal nodal staging in patients with suspected or proven non-small-cell peripheral lung cancer without mediastinal involvement at CT or CT-PET, we suggest that EBUS-TBNA and/or EUS-(B)-FNA should be performed before therapy, provided that one or more of the following conditions is present: (i) enlarged or fluorodeoxyglucose (FDG)-PET-avid ipsilateral hilar nodes; (ii) primary tumor without FDG uptake; (iii) tumor size ≥ 3 cm (Fig. 3a - c) (Recommendation grade C). If endosonography does not show malignant nodal involvement, we suggest that mediastinoscopy is considered, especially in suspected N1 disease (Recommendation grade C). If PET is not available and CT does not reveal enlarged hilar or mediastinal lymph nodes, we suggest performance of EBUS-TBNA and/or EUS-(B)-FNA and/or surgical staging (Recommendation grade C). 3 In patients with suspected or proven < 3 cm peripheral NSCLC with normal mediastinal and hilar nodes at CT and/or PET, we suggest initiation of therapy without further mediastinal staging (Recommendation grade C). 4 For mediastinal staging in patients with centrally located suspected or proven NSCLC without mediastinal or hilar involvement at CT and/or CT-PET, we suggest performance of EBUS-TBNA, with or without EUS-(B)-FNA, in preference to surgical staging (Fig. 4) (Recommendation grade D). If endosonography does not show malignant nodal involvement, mediastinoscopy may be considered (Recommendation grade D). 5 For mediastinal nodal restaging following neoadjuvant therapy, EBUS-TBNA and/or EUS-(B)-FNA is suggested for detection of persistent nodal disease, but, if this is negative, subsequent surgical staging is indicated (Recommendation grade C). 6 A complete assessment of mediastinal and hilar nodal stations, and sampling of at least three different mediastinal nodal stations (4 R, 4 L, 7) (Fig. 1, Fig. 5) is suggested in patients with NSCLC and an abnormal mediastinum by CT or CT-PET (Recommendation grade D). 7 For diagnostic purposes, in patients with a centrally located lung tumor that is not visible at conventional bronchoscopy, endosonography is suggested, provided the tumor is located immediately adjacent to the larger airways (EBUS) or esophagus (EUS-(B)) (Recommendation grade D). 8 In patients with a left adrenal gland suspected for distant metastasis we suggest performance of endoscopic ultrasound fine needle aspiration (EUS-FNA) (Recommendation grade C), while the use of EUS-B with a transgastric approach is at present experimental (Recommendation grade D). 9 For optimal endosonographic staging of lung cancer, we suggest that individual endoscopists should be trained in both EBUS and EUS-B in order to perform complete endoscopic staging in one session (Recommendation grade D). 10 We suggest that new trainees in endosonography should follow a structured training curriculum consisting of simulation-based training followed by supervised practice on patients (Recommendation grade D). 11 We suggest that competency in EBUS-TBNA and EUS-(B)-FNA for staging lung cancer be assessed using available validated assessment tools (Recommendation Grade D).